Religiosity, Lifestyle, and Sharia Financial Literacy on Paylater Usage Behaviour - Harahap, Mhd. Rivaldhy; Hasibuan, Reni Ria Armayani; Nur Ahmadi Bi Rahmani (Islamic Economics and finance in Focus, 2026)
This study aims to analyse the influence of religiosity, lifestyle and Sharia financial literacy on paylater usage behaviour in North Sumatra. This study employs a quantitative approach using a survey method involving 100 students from the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra who have used or are currently using paylater services. The data were analysed using multiple linear regression with the aid of SPSS. The results indicate that, taken together, all independent variables have a significant influence on ‘PayLater’ usage behaviour. However, when analysed individually, only religiosity has a significant influence, whilst lifestyle and Sharia financial literacy do not have a significant influence. These findings indicate the existence of a gap between religious values and financial behaviour (value-behaviour gap), whereby a high level of religiosity is not always accompanied by financial practices that conform to Sharia principles. The coefficient of determination of 0.506 indicates that the research model has a reasonably strong explanatory power. This study makes an empirical contribution to understanding the use of ‘paylater’ services among Muslim students and emphasises that the implementation of religious values and Sharia financial literacy needs to be strengthened in a more practical manner in order to foster financial behaviour that is in line with the principles of Islamic economics.